Early career choices and successful career progression in surgery in the UK: prospective cohort studies - Goldacre, M; Laxton, L; Harrison, E; Richards, J; Lambert, T; Parks, R (BioMed Central, 2010)
Background: Changes to the structure of medical training worldwide require doctors to decide on their career specialty at an increasingly early stage after graduation. We studied trends in career choices for surgery, and the eventual career destinations, of UK graduates who declared an early preference for surgery. Methods: Postal questionnaires were sent, at regular time intervals after qualification, to all medical qualifiers from all UK medical schools in selected qualification years between 1974 and 2005. They were sent in the first year after qualification, at year three and five years after qualification, and at longer time intervals thereafter. Results: Responses were received from 27 749 of 38 280 doctors (73%) at year one, 23 468 of 33151 (71%) at year three, and 17 689 of 24 870 (71%) at year five. Early career preferences showed that surgery has become more popular over the past two decades. Looking forward from early career choice, 60% of respondents (64% of men, 48% of women) with a first preference for a surgical specialty at year one eventually worked in surgery (p < 0.001 for the male-female comparison). Looking backward from eventual career destinations, 90% of responders working in surgery had originally specified a first choice for a surgical specialty at year one. 'Match' rates between eventual destinations and early choices were much higher for surgery than for other specialties. Considering factors that influenced early specialty choice 'a great deal', comparing aspiring surgeons and aspiring general practitioners (GPs), a significantly higher percentage who chose surgery than general practice specified enthusiasm for the specialty (73% vs. 53%), a particular teacher or department (34% vs. 12%), inclinations before medical school (20% vs. 11%), and future financial prospects (24% vs. 13%); and a lower percentage specified that hours and working conditions had influenced their choice (21% vs. 71%). Women choosing surgery were influenced less than men by their inclinations before medical school or by their future financial prospects. Conclusions: Surgery is a popular specialty choice in the UK. The great majority of doctors who progressed in a surgical career made an early and definitive decision to do so.